2010
DOI: 10.3892/or_00000826
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and alterations in DNA repair proteins in the SW480 colorectal cancer cell line

Abstract: Abstract. Regular aspirin intake is associated with a reduction in the incidence of colorectal cancer. Aspirin has been shown to be cytotoxic to colorectal cancer cells in vitro. The molecular basis for this cytotoxicity is controversial, with a number of competing hypotheses in circulation. One suggestion is that the protective effect is related to the induction of expression of the DNA mismatch repair (MMR) proteins hMLH1, hMSH2, hMSH6 and hPMS2 in DNA MMR proficient cells. We report that treatment of the DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Accumulating evidence suggests that the abnormal acetylation of DNA repair proteins contributes to the impairment of DNA repair mechanisms, the development and progression of cancer, and the sensitivity of cancer cells to chemotherapy. These insights into the role of acetylation and its implications in cancer have been reported previously [20,28]. In the present study, we treated PEO14 cells with 3 mM aspirin for 24 h to induce hyperacetylation, which did not result in cytotoxic effects.…”
Section: Discussionsupporting
confidence: 76%
“…Accumulating evidence suggests that the abnormal acetylation of DNA repair proteins contributes to the impairment of DNA repair mechanisms, the development and progression of cancer, and the sensitivity of cancer cells to chemotherapy. These insights into the role of acetylation and its implications in cancer have been reported previously [20,28]. In the present study, we treated PEO14 cells with 3 mM aspirin for 24 h to induce hyperacetylation, which did not result in cytotoxic effects.…”
Section: Discussionsupporting
confidence: 76%
“…The first group includes primary genes controlled directly by aspirin, i.e., PTGS2 and PTGES2 . The second group consists of genes involved in cell signaling and cell proliferation like cMyc , EGFR , BCL2 , WNT , KRAS , WNT6 , BRAF , MUC1 , PIK3CA , PARP1 , PARP2 , STAT3 , MAPK , JAK/STAT , and BAX [ 6 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]; the third group includes genes for cytokines or their receptors (e.g., IFNγ , IL1β , IL2 , IL4 , IL5 , IL6 , IL7 , IL8 , IL10 , IL12 (p70) , IL13 , IL17 , CXCR1 , CXCR2 , PTGS2 , PTGES2 , NFKB1 , and TNFα ) [ 30 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]; and the fourth group consists of tumor suppressor genes including P53 , BRCA1 [ 43 ], hMLH1 , hMSH2 , hMSH6 , and hPMS2 [ 44 , 45 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies have shown that aspirin can affect DNA repair of genes. For example, treatment of a DNA MMR competent/p53 mutant colorectal cancer cell line with aspirin for 48 h led to DNA damage pathway gene expression, including BRCA1 [ 45 ]. A later study found that feeding aspirin to Dalton cell lymphoma-bearing mice resulted in cell cycle arrest in the G0/G1 phase [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Induced alterations in the expression profile of gene transcripts do not necessarily correlate with expression of their respective encoded proteins 45 . Moreover, post-translational modifications of encoded gene products are not taken into account by microarrays and qRT-PCR techniques.…”
Section: Resultsmentioning
confidence: 99%